2014
DOI: 10.5012/bkcs.2014.35.5.1375
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Directed Synthesis of γ-Fe2O3Nanoparticles and Their Magnetic Properties Investigation

Abstract: In this study, maghemite (γ-Fe 2 O 3 ) nanoparticles were produced using gelatin protein as an effective mediator. Size, shape, surface morphology and magnetic properties of the prepared γ-Fe 2 O 3 nanoparticles were characterized using XRD, FT-IR, TEM, SEM and VSM data. The effects of furnace temperature and time of heating together with the amount of gelatin on the produced gelatin-Fe 3 O 4 nanocomposite were examined to prove the fundamental effect of gelatin; both as a capping agent in the nanoscale synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…All these are in favour of large adsorption capacity. The colour of the nanoparticles has changed from black to brown, for some Fe 3 O 4 nanoparticles' oxidation to γ-Fe 2 O 3 [25]. The results showed that when 2θ is in the range of 5~80°, the six characteristic peaks of Fe 3 O 4 (2θ=30.1°, 35.5°, 43.1°, 53.4°, 57.0°, 62.6°) existed.…”
Section: Morphology Characterizationmentioning
confidence: 97%
See 4 more Smart Citations
“…All these are in favour of large adsorption capacity. The colour of the nanoparticles has changed from black to brown, for some Fe 3 O 4 nanoparticles' oxidation to γ-Fe 2 O 3 [25]. The results showed that when 2θ is in the range of 5~80°, the six characteristic peaks of Fe 3 O 4 (2θ=30.1°, 35.5°, 43.1°, 53.4°, 57.0°, 62.6°) existed.…”
Section: Morphology Characterizationmentioning
confidence: 97%
“…In aqueous solution, the template protein and functional monomer can form complex through the -OH of the monomer and amino acid of the protein. However, 25 decreasing cross-linking increases spatial fluctuations in the recognition sites and hence reduces binding efficiency. The Fe 3 O 4 @GO@MIP nanoparticles were fixed on the Au electrode in this way (Fig.1).…”
Section: Electrochemical Detectionmentioning
confidence: 99%
See 3 more Smart Citations